A study on vibration of tapered non-homogeneous rectangular plate with structural parameters - Kaur, Narinder; Singhal, A.; Khanna, A. (Zielona Góra: Uniwersytet Zielonogórski)
Effects of structural parameters on the vibration of a tapered non-homogeneous rectangular plate with different combinations of boundary conditions are discussed. Tapering in the plate is assumed to be sinusoidal in the x-direction. Here, temperature variation and non-homogeneity in the plate material are also considered sinusoidal in the x-direction.
Keywords: vibrations; non-homogeneity; thermal gradient; taper parameter; clamped; simply supported; aspect ratio